الشراكة كآلية لتفعيل دور الجماعات المحلية - قادري, رضوان (University of Eloued جامعة الوادي, 2022)
تهدف هذه الد ا رسة الى تسليط الضوء على موضوع الش ا ركة بشقيها سوى الش ا ركة المجتمعية او الاقتصادية و اهميتها كآلية لتفعيل عمل الجماعات المحلية حيث تهدف الى تحقيق تنمية محلية مستدامة، حيث تعتبر الش ا ركة اسلوبا مستحدثا للتسيير تسلكه العديد من دول العالم، تقوم على مبدأ إش ا رك المواطن في تسيير الشأن المحلي, بعدما اثبتت المقاربة التمثيلية اخفاقها ومحدوديتها في التعبير عن امال الاف ا رد و تطلعاتهم، حيث تم تقديم آلية الش ا ركة الحقيقية كمكملة للمقاربة المحلية, و ليس كبديل عنها او منافس لها، كونها تستند على دور الفواعل كالمجتمع المدني والقطاع الخاص، اذ ان الش ا ركة الاقتصادية تعتمد اساسا على فتح المجال امام القطاع الخاص و الاستفادة من خدماته في انشاء و تسيير و صيانة مشروعات تخدم المواطن المحلي وتلبي حاجياته في نفس الوقت تزيح العبء، حيث توصلت الد ا رسة الى الدور الذي يلعبه المجتمع المدني اذ استحدث له هيئة استشارية لدى رئيس الجمهورية في تعديل الدستوري 2020 بما يعرف بالمرصد الوطني للمجتمع المدني من اجل ش ا ركة حقيقية تفعل عمل الجماعات المحلية توصلت الد ا رسة ايضا الى اهمية التفويض و التسيير التشاركي في تحسين و جودة الخدمات المقدمة.This study aims to shed light on the issue of partnership, in both its two parts, the socio and economic partnership, and its importance as a mechanism for activating the work of local groups to achieve sustainable local development, Where partnership is considered an innovative method of management adopted by many countries of the world, based on the principle of involving the citizen in managing local affairs, after the representative approach proved its failure and limitations in expressing the hopes and aspirations of individuals, as the real partnership mechanism was presented as a complement to the local approach, and not as a substitute for it Or a competitor to it, as it is based on the role of actors such as civil society and the private sectoras the economic partnership is based on allowing the private sector to participate in the establishment, management, and maintenance of projects that serve the local citizen and meet their needs while at the same time removing the burden. the study concluded the role performed by civil society, as it created an advisory body to the President of the Republic. which is known as the Observatory, The study also found the importance of delegation and participatory management in improving the quality of services provided.
مذكرة ماستر